PENGARUH POLA ASUH ORANG TUA TERHADAP PERILAKU BERAGAMA DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS V SD SE-GUGUS PULAU KIJANG KECAMATAN RETEH INHIL RIAU - Yulisna Yulisna; Munawar Rahmat; Edi Suresman (Millah: Journal of Religious Studies, 2016)
This research is aimed to answer the question how is parenting and how is the influence toward religious behavior and learning outcome of students in Islamic Religious Education Subject in Class V Elementary School in whole cluster of Kijang Island, Reteh Inhil Sub District, Riau.  The method of study used is mixed method, by combining quantitative and qualitative approach.  Sampling use cluster sampling technique with total of 80 students and 80 parents.  Quantitative data is processed by SPSS 20.0.  Result of study showed that in fact, parenting determine the high and the low of religious behavior and learning outcome of Islamic Religious Education in students. Children with high and medium religious behavior are educated by parents who have authoritative parenting style. Whereas children with low religious behavior are they who are educated by authoritarian parenting, authoritative, permissive, combination of authoritarian-authoritative and combination of authoritative-permissive. Likewise, the results PAI study, children who have a high learning outcomes educated by parents who patterned authoritative parenting. While the children medium are educated  by authoritarian parenting, authoritative, permissive, combination of authoritarian-authoritative and combination of authoritative-permissive.With this study, it is expected that Islamic Religious Education teachers continually upgrade their ability to understand science of child psychology and pay attention to children diversity not only on cognitive value.